Acousto-optic modulators of high-power laser radiation on the basis of KGW and KYW crystals. (October 2020) - Mazur, M.M.; Mazur, L.I.; Sirotkin, A.A.; Ryabinin, A.V.; Shorin, V.N.
Abstract: Different modifications of acousto-optic modulators (AOMs) based on KG(WO4 )2 (KGW) and KY(WO4 )2 (KYW) crystals, designed for Q switching of high-power pulsed lasers, is developed and investigated. It is shown that AOMs based on these crystals are universal, can be combined with different lasers in the wavelength range of 1 – 3 μm, and have a high radiation resistance in the absence of antireflection coatings and light input at Brewster's angle. The operation efficiency of KGW-based AOMs is experimentally demonstrated. Solid-state lasers based on Cr : Er : YSGG ( λ = 2.78 μm), Cr : Yb : Ho : YSGG ( λ = 2.87 μm), Cr : Tm : Ho : YSGG ( λ = 2.09 μm), and Nd : YAG ( λ = 1.064 μm) crystals with active acousto-optic Q switching, operating in the repetitively pulsed regime with a high beam quality and without surface destruction, are investigated. Lasing pulses (30 – 60)-ns long with energy up to 32 mJ at a repetition rate from 1 to 1000 Hz are obtained.